Medicinal plants used in the treatment of maternal health-related problems by the Mapulana of Ehlanzeni District, Mpumalanga province, South Africa - Shalom Pabalelo Mashile, Milingoni Peter Tshisikhawe, Ndivhaleni Anox Masevhe (Journal of Applied Pharmaceutical Science, 2019)
A decreased mortality rate among infants and children has been a health target for most health facilities. South Africa’s free maternal healthcare services are not adequately utilized due to the tradition of new mothers following their parents’ footsteps. The use of medicinal plant species in maternal healthcare has been perceived to be effective and reliable in preventing illness among communities. For this study, ethnobotanical data were collected by means of interviews using semi-structured questions responded to by the elderly, community adults, and youth who had been selected on the basis of referrals. Infants within the communities have been treated with traditional medicine for ailments, such as colic, nail biting, sunken, and bulging fontanelles. Hypoxis hemerocallidea Fisch., C. A. Mey. & Ave-Lall, Lippia javanica (Burm.f.) Spreng., Vachellia karroo (Hayne) Banfi & Glasso, and Annona senegalensis Pers. subsp. senegalensis were among plant species which were frequently reported as being used medicinally. The decoction was mostly prepared from the roots (79%) followed by bulbs (8%) and most of the decoction was taken orally. The study identified 13 plant species used successfully for the treatment of bulging and sunken fontanelles.
Keywords: Maternal healthcare, bulging, sunken fontanelles.